TEKNIK EVALUASI PEMBELAJARAN PAI JENJANG SEKOLAH MENENGAH PERTAMA - alfiana, rizka; Nasikhin, Nasikhin; Kotrunada, Aliza Kotrunada; Wibowo, Ibnu Qowi; Adila, Isti Nusrotal; Junaedi, Mahfud (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
The study is aimed at analyzing the model of application of PAI learning evaluation techniques in the upper secondary school. Using qualitative methods, the study uses a narative inquiry approach that collects data through interviews and group discussions. The results of this study show that the method of evaluation of upbringing in secondary school is a tool to measure the understanding of students in the learning-teaching process. Using various methods such as physical response methods, Indonesian Realistic Mathematical Learning Approach (PMRI), and project basic learning approaches, teachers can identify individual student needs and harmonize teaching to better suit. Implementation of learning evaluation is carried out through several stages namely; determining the objectives of evaluation, defining the design of evaluations, developing evaluation instruments, collection of information/data, analysis and interpretation and follow-up determining appropriate instruments according to the objective to be achieved. The purpose of learning evaluation is to know the development of the student's skills in learning as well as the success of the delivery of material performed by the teacher. This study gives implications for the effective assessment of the learning of Islamic Religious Education in the First Secondary School.